2016
DOI: 10.1093/cid/ciw023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hepatitis B Virus Persistence in Hepatocytes and Its Carcinogenic Potential

Abstract: Liver disease associated with persistent infection with hepatitis B virus (HBV) continues to be a major health problem of global impact. Despite the existence of an effective vaccine, at least 240 million people are chronically infected worldwide, and are at risk of developing liver cirrhosis and hepatocellular carcinoma. Although chronic HBV infection is considered the main risk factor for liver cancer development, the molecular mechanisms determining persistence of infection and long-term pathogenesis are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“…Similarly, the character of DCH-associated HCC shared features with hepatopathies caused by HBV and/or woodchuck hepatitis virus, including regions of vacuolar change and individual hepatocellular necrosis, although individual histologic features of HCC did not distinguish DCH-positive from DCH negative cases. Greater hepatocyte proliferation observed in DCH-associated areas of HCC compared with virus negative regions is worthy of note since hepatocyte proliferation driven by the host immune response contributes to hepatocyte transformation in HBV-associated HCC [11]. The consistency of this finding should now be tested in a larger number of DCH-associated HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the character of DCH-associated HCC shared features with hepatopathies caused by HBV and/or woodchuck hepatitis virus, including regions of vacuolar change and individual hepatocellular necrosis, although individual histologic features of HCC did not distinguish DCH-positive from DCH negative cases. Greater hepatocyte proliferation observed in DCH-associated areas of HCC compared with virus negative regions is worthy of note since hepatocyte proliferation driven by the host immune response contributes to hepatocyte transformation in HBV-associated HCC [11]. The consistency of this finding should now be tested in a larger number of DCH-associated HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Liver cancer is the fourth most common malignant tumor in the world and the third leading cause of cancer-associated death (1). China has a high incidence of chronic hepatitis B, and persistent infection and replication of hepatitis B virus causes liver fibrosis and cirrhosis or possibly liver cancer as the diseases progresses (2). A recent analysis reported that 45.69% of liver cancer deaths were due to HBV infection, so the incidence and mortality of hepatocellular carcinoma (HCC) is high as a result (3).…”
Section: Introductionmentioning
confidence: 99%
“…More than 600 000 people die from HBV infection each year . At present, although the nucleotide analogues (NAs) drugs and interferon have been widely used in the treatment of HBV infection, HBV‐related diseases have not been effectively controlled . Therefore, exploring the molecular mechanism of viral replication and pathogenesis is urgently needed, and more attention should be paid to the study of HBV virological features, such as replication, life cycle and mutation.…”
Section: Discussionmentioning
confidence: 99%